Kelimpahan dan Biomassa Ikan Karang di Kawasan Konservasi Perairan Gili Balu, Kabupaten Sumbawa, Nusa Tenggara Barat - Himawan, Mahardika Rizqi; Hidayatullah, Rahmat; Prabuning, Derta; Lestariningsih, Wiwid Andriyani (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
The Gili Balu Marine Conservation Area (KKP), located in Sumbawa Regency, West Nusa Tenggara, is ecologically and economically significant due to its rich coral reef ecosystems. This research aims to measure the abundance and biomass of reef fish in the KKP Gili Balu, which can be used as a basis for evaluating the effectiveness of conservation efforts in maintaining marine biodiversity. The Underwater Visual Census (UVC) method was used, recording types of reef fish at ten observation points. The results showed that the highest abundance was found on Mandiki Island, with functional fish abundance reaching 2973 ind/ha, followed by Pasareang Barat Island (1903 ind/ha) and South Kalong (1600 ind/ha). The biomass of functional fish also reflects their important role in maintaining the balance of the coral reef ecosystem. This research contributes to the scientific understanding of marine biodiversity in the KKP Gili Balu and provides a basis for sustainable conservation management efforts. Additionally, the research recorded the presence of several coralivorous and economically important fish species, although they tend to be smaller compared to functional fish. Economically important fish in the KKP Gili Balu waters were found only at four observation locations: East Belang Island, North Belang, Kenawa, and Southwest Namo. The highest value was recorded at Kenawa Island, with 93 ind/ha. These fish tend to be rare in this area, possibly due to past fishing practices.